2021
DOI: 10.3390/infrastructures7010004
|View full text |Cite
|
Sign up to set email alerts
|

Energy Resilience Impact of Supply Chain Network Disruption to Military Microgrids

Abstract: The ability to provide uninterrupted power to military installations is paramount in executing a country’s national defense strategy. Microgrid architectures increase installation energy resilience through redundant local generation sources and the capability for grid independence. However, deliberate attacks from near-peer competitors can disrupt the associated supply chain network, thereby affecting mission critical loads. Utilizing an integrated discrete-time Markov chain and dynamic Bayesian network approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 115 publications
0
2
0
Order By: Relevance
“…Ripple effects occur when the impacts of an event cascade throughout the supply chain instead of remaining confined to a single node or portion of the network (Anuat, Bossuyt, and Pollman, 2022). Their propagation across the supply chain can further amplify the initial impact beyond what might reasonably be anticipated (Xiong et al, 2020).…”
Section: Ripple Effects Of Risks and Disruptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ripple effects occur when the impacts of an event cascade throughout the supply chain instead of remaining confined to a single node or portion of the network (Anuat, Bossuyt, and Pollman, 2022). Their propagation across the supply chain can further amplify the initial impact beyond what might reasonably be anticipated (Xiong et al, 2020).…”
Section: Ripple Effects Of Risks and Disruptionsmentioning
confidence: 99%
“…Supply chain disruptions are not new but have been brought to public attention most visibly by the large-scale effects on supply chains resulting from the volcanic eruptions in Iceland (2010), the coronavirus disease 2019 (COVID-19) pandemic (2020 onwards), and, most recently, the cascading impacts of the war in Ukraine (February 2022 and ongoing); these disruptions have often been exacerbated by contemporaneous and unpredicted spikes in demand. These and other disruptive events have clearly demonstrated that disruptions can propagate through supply chains more quickly than decisionmakers can effectively respond to them and can cripple companies' operations and deliveries of products (Abogaye et al, 2022;Jones, 2022;Anuat, Van Bossuyt, and Pollman, 2022;Hitchens, 2020;Janes Intelligence Briefings, 2020;CNBC, 2019;Ferry and Poindexter, 2016). This disruption can be detrimental and even catastrophic to economic activity and can have highly damaging impacts on defense operations and the ability of armed forces to carry out their tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Even if the military base is prepared, any vulnerabilities in the local community will spill over because most military personnel and their families live off base in the local community. The military base would find itself in the position of having to support the local community [10].…”
Section: Resilience Modeling Incorporating Climate Changementioning
confidence: 99%
“…Miramar and Twentynine Palms are grid-connected microgrids [31]. Microgrids may include renewable energy resources [12,36], which may increase resilience by withstanding disruptions due to fuel supply disruptions such as the 2021 Colonial Pipeline cyberattack which crippled fuel deliveries across its 5500-mile length along the United States east coast [37,38]. The literature includes methods for microgrid design to consider resilience as well as capacity, cost, reliability and sustainability with diesel generators, photovoltaic (PV) sources, battery energy storage system (BESS), and energy management system (EMS) components [5,39].…”
Section: Microgridsmentioning
confidence: 99%